A Pilot Study of a Randomized Controlled Trial of Yoga as an Intervention for PTSD Symptoms in Women. Issue 2 (25th March 2014) - Mitchell, Karen S.; Dick, Alexandra M.; DiMartino, Dawn M.; Smith, Brian N.; Niles, Barbara; Koenen, Karestan C.; Street, Amy
<x xml:space="preserve">Abstract</x> Posttraumatic stress disorder (PTSD) is a debilitating condition that affects approximately 10% of women in the United States. Although effective psychotherapeutic treatments for PTSD exist, clients with PTSD report additional benefits of complementary and alternative approaches such as yoga. In particular, yoga may downregulate the stress response and positively impact PTSD and comorbid depression and anxiety symptoms. We conducted a pilot study of a randomized controlled trial comparing a 12‐session Kripalu‐based yoga intervention with an assessment control group. Participants included 38 women with current full or subthreshold PTSD symptoms. During the intervention, yoga participants showed decreases in reexperiencing and hyperarousal symptoms. The assessment control group, however, showed decreases in reexperiencing and anxiety symptoms as well, which may be a result of the positive effect of self‐monitoring on PTSD and associated symptoms. Between‐groups effect sizes were small to moderate (0.08–0.31). Although more research is needed, yoga may be an effective adjunctive treatment for PTSD. Participants responded positively to the intervention, suggesting that it was tolerable for this sample. Findings underscore the need for future research investigating mechanisms by which yoga may impact mental health symptoms, gender comparisons, and the long‐term effects of yoga practice.